Knowledge and adherence to antiretroviral therapy among adult people living with HIV/AIDS at Tikur Anbessa Specialized Hospital, Ethiopia - Demessie, Ruth; Mekonnen, Alemayehu; Amogne, Wondwossen; Shibeshi, Workineh (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Adherence to antiretroviral therapy (ART) is necessary to achieve best virological response, lower the risk of drug resistance, and reduce morbidity and mortality. The objectives of the current study were to assess the extent of knowledge of patients on treatment plan and regimen, determine the rate of adherence and identify factors related to non-adherence to ART. Methods: A cross-sectional study was conducted at Tikur Anbessa Specialized Teaching Hospital, Addis Ababa, Ethiopia, using data from both semi-structured interview (self-report) and ART database (pharmacy refill) during the months of March and April 2013 using a total 350 participants. Results: The results indicated that 33% of the participants had good knowledge on the treatment plan and regimen. Using self-report and pharmacy refill record, 79.1% and 72.9% respectively showed adherence rate of ≥95%. Younger people were found to be less likely to adhere to ART (AOR [95%] = 0.51 [0.30, 0.85]) using pharmacy refill record. Risk factors for ART non-adherence using self-report were use of memory aids (AOR [95%] = 3.46 [1.72, 6.98]), treatment satisfaction (AOR [95%] = 2.33 [1.22, 4.07]), taking co-medication (AOR [95%] = 0.56 [0.32, 0.98]), and regimen switch (AOR [95%] = 0.41 [0.19, 0.85]). Whereas using pharmacy refill record risk factors were, knowledge on treatment plan and regimen (AOR [95%] = 2.50 [1.39, 4.51]), use of memory aids (AOR [95%] = 2.71 [1.34, 5.47]), treatment satisfaction (AOR [95%] = 3.78 [1.47, 9.71]), and regimen switch (AOR [95%] = 0.50 [0.27, 0.92]). Conclusion: Older age, good knowledge on treatment plan and regimen, use of memory aids, treatment satisfaction, and not having co-medications and regimen switch showed more adherence to ART.